A preliminary study of an eastern Mediterranean coastal ecosystem: Summer Resorts and Benthic ecosystems - REIZOPOULOU, S.; ZENETOS, A. (Mediterranean Marine Science, 2006)
The present study investigates whether coastal benthic communities are affected by tourist activities along the coast, which persist for a limited time period. The analysis of benthic macrofauna is based on the ecological parameters (quantitative analyses) as well as on the ecological identity of the species (qualitative analyses). Microbial contamination and some population statistics are correlated with ecological parameters. The disturbance of benthic communities in the vicinity of summer resorts is summarized by a reduction in species number and dominance of opportunistic species characteristic of disturbed and polluted environments. It is found that community diversity and evenness of distribution decrease with the deterioration of water quality, expressed as grade of microbial contamination, which implies that benthic community is also a significant element in assessing the quality of coastal waters. The above parameters were statistically negatively correlated with the number of tourists.